EFFORTS TO INCREASE STUDENT LEARNING OUTCOMES BY USING PROJECT WORKING METHODS IN CLASS IV IPS SUBJECTS AT SDN 13 KOTO BESAR : UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MEGGUNAKAN METODE KERJA PROYEK PADA MATA PELAJARAN IPS KELAS IV DI SDN 13 KOTO BESAR - ruminah ruminah (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2022)
In relation to the social studies learning process, the author has carried out the social studies learning process with the material to improve student learning outcomes by using a project work learning model on social studies subjects in grade IV SD Negeri 13 Koto Besar. Social work by using the project work method can give students enthusiasm in learning and avoid the monotonous teaching and learning process. The percentage of mastery learning applied in learning outcomes to the subject matter discussed in the pre-cycle is only 50%, and in the first cycle the value of the new child is 65%, and in the second cycle 95%. Thus it is considered successful because of an increase in student learning outcomes by 45%.